Study to Evaluate Coronary Artery Disease Prevalence and Risk Factors in Heart Failure Patients with Reduced Ejection Fraction - Paudel, Navaraj; Thapa, Namrata (Nepal Journal of Medical Sciences, 2022)
Introduction: Even though heart failure (HF) is a major global health problem, studies on the prevalence and etiology of HF in Nepal are scant. The aim of this study was to assess the prevalence and risk factors of coronary artery disease (CAD) in HF with reduced ejection fraction (HFrEF) using invasive coronary angiography (CAG). Methods: This was a prospective, cross-sectional, descriptive observational study conducted from July 2020 to September 2021. All consecutive patients with HFrEF who met the inclusion criteria underwent CAG at Manipal Teaching Hospital were evaluated and analyzed using various statistical tools. Results: Total 108 patients with a male to female ratio of 2.02:1 were assessed. The mean age of patients was 63+6.08 years. The prevalence of CAD was 72% of which 42% were having significant CAD (stenosis >50%) with 45%, 32% and 23% having triple (TVD), double (DVD) and single vessel disease (SVD) respectively Smoking was the commonest risk factor (61%) followed by hypertension (52%), dyslipidemia (27%) and diabetes (22%). The prevalence of CAD increased with increase in the number of risk factors. There was significant association of smoking (OR: 11.5, P: 0.005), hypertension (OR: 8.5, P: 0.002) and diabetes (OR: 10, P: 0.001) for occurrence of significant CAD. Conclusion: In our study, otherwise unexplained HFrEF showed overall 72% of CAD with 42% having significant CAD (stenosis >50%). Conventional risk factors like smoking, hypertension and diabetes were significantly associated with development of CAD.